Unmasking the effects of orthography, semantics, and phonology on 2AFC visual word perceptual identification. Issue 10 (26th November 2021) - Kress, Shaylyn; Neudorf, Josh; Ekstrand, Chelsea; Borowsky, Ron
ABSTRACT: In the two-alternative forced-choice (2AFC) task, the target stimulus is presented very briefly, and participants must choose which of two options was the presented target. Some past research has assumed that the 2AFC task isolates orthographic effects, despite orthographic, semantic, and phonological differences between the options. If so, performance should not differ between word/nonword pairs and British/American word pairs, the latter of which only differ orthographically. In Experiment 1, accuracy and sensitivity were higher during word/nonword trials than British/American trials when participants did not guess, demonstrating that phonological/semantic processing contributes to performance. Experiment 2 showed that target visibility did not interact with pair type on RT, which suggests phonological/semantic processing did not feed back to orthographic encoding in this task. This study demonstrates the influence of phonological/semantic processing on word perceptual identification, and shows that using British/American word pairs provides a method to isolate orthography in the 2AFC task.